2018 update of the EULAR recommendations for the role of the nurse in the management of chronic inflammatory arthritis. Issue 1 (12th July 2019) - Bech, Bianca; Primdahl, Jette; van Tubergen, Astrid; Voshaar, Marieke; Zangi, Heidi A; Barbosa, Lurdes; Boström, Carina; Boteva, Boryana; Carubbi, Francesco; Fayet, Françoise; Ferreira, Ricardo J O; Hoeper, Kirsten; et al.
Abstract : To update the European League Against Rheumatism (EULAR) recommendations for the role of the nurse in the management of chronic inflammatory arthritis (CIA) using the most up to date evidence. The EULAR standardised operating procedures were followed. A task force of rheumatologists, health professionals and patients, representing 17 European countries updated the recommendations, based on a systematic literature review and expert consensus. Higher level of evidence and new insights into nursing care for patients with CIA were added to the recommendation. Level of agreement was obtained by email voting. The search identified 2609 records, of which 51 (41 papers, 10 abstracts), mostly on rheumatoid arthritis, were included. Based on consensus, the task force formulated three overarching principles and eight recommendations. One recommendation remained unchanged, six were reworded, two were merged and one was reformulated as an overarching principle. Two additional overarching principles were formulated. The overarching principles emphasise the nurse's role as part of a healthcare team, describe the importance of providing evidence-based care and endorse shared decision-making in the nursing consultation with the patient. The recommendations cover the contribution of rheumatology nursing in needs-based patient education, satisfaction with care, timely access to care, disease management, efficiency of care, psychosocial support and the promotion of self-management. The level of agreement among task force members was high (mean 9.7, range 9.6-10.0). The updated recommendations encompass three overarching principles and eight evidence-based and expert opinion-based recommendations for the role of the nurse in the management of CIA.